Nachhaltige Nicht-Nachhaltigkeit: Warum die ökologische Transformation der Gesellschaft nicht stattfindet - Butzlaff, Felix; Blühdorn, Ingolfur; Deflorian, Michael; Hausknost, Daniel; Mock, Mirijam (transcript, 2020)
Even though environmental movements demand that "Continuing this way is not an option!", modern society is defending its prosperity and lifestyle more decisively than ever before. A policy of non-sustainability is persistently pursued, and the boom of right-wing populism also signals a clear departure from the ecological-democratic project of past decades.This volume questions fundamental assumptions of the sustainability debate and outlines new social science research perspectives in order to shed light on the peculiar persistence of non-sustainability.